THE POPULATION SUCCESSION PATTERNS OF CABBAGE MAIN PEST Plutella xylostella L. AND Crocidolomia pavonana Fab AT CABBAGE PLANTATION - Yuliadhi, Ketut Ayu; Supartha, I Wayan; Wijaya, I Nyoman; Pudjianto, Pudjianto (International Journal of Biosciences and Biotechnology; Vol 3 No 1 (2015), 2016)
This study was aimed to investigate the population dynamics of the cabbage insect pests, Plutella xylostella and Crocidolomia pavonana under natural conditions. The population succession patterns of both pests were determined by observing the abundance of their population on a regular basis from the beginning to the end of the planting season. Understanding the population succession patterns of P. xylostella and C. pavonana will give an idea the shifting time by both pests on attacking the crops, therefore on deciding the time of controlling. The population succession patterns occur in 8 weeks of planting season. P. xylostella dominated the cabbage plants when they were 1-5 weeks after planting (WAP), but when the cabbage plants were more than 5 weeks old they were dominated by C pavonana.
Keywords: Crocidolomia pavonana; cabbage; Plutella xylostella; succession